Spatial and temporal variation of fish assemblage associated with aquatic macrophyte patches in the littoral zone of the Ayapel Swamp Complex, Colombia (2017)
ABSTRACT: Aim: The purpose of the present study was to examine spatial and temporal variation in fish assemblage structure associated with aquatic macrophytes in the littoral zone of the ASC. Methods: Specimens were caught between January 2008 and February 2009, over four limnimetric moments, using both cast net and seine net. Data on the temperature, electrical conductivity, pH and dissolved oxygen was recorded for the characterization of the water mass in the sites. Results: A total of 34,151 specimens from 44 species were collected. The most abundant species were Eigenmannia virescens, Astyanax caucanus, Astyanax fasciatus, Roeboides dayi and Cyphocharax magdalenae, which together accounted for more than 75% of the sample. Temporal and spatial comparisons showed variation in the environmental conditions and highlighted the existence of heterogeneous abiotic conditions (p<0.05). However, the multiple comparisons test showed the existence of homogeneous spatial conditions (p>0.05) regarding the fish assemblage structure. The multivariate analysis showed no significant relationship between existing environmental conditions and the fish assemblage (p=0.04). The analysis also showed the absence of a relationship between the fish assemblage and environmental variables with respect to the flood pulse and sampling sites (p>0.05). Conclusion: The uniformity of the fish communities that inhabit aquatic macrophyte patches in the littoral region of the ASC may be related to the availability of suitable habitat in structural terms, that probably supports a more abundant and varied wildlife.